2008
DOI: 10.1080/17549500701855133
|View full text |Cite
|
Sign up to set email alerts
|

Vowel transcription systems: An Australian perspective

Abstract: Transcription is an essential clinical tool for speech-language pathologists as it provides a permanent written record of communicative behaviour and forms an important source of data for analysis, interpretation, decision making, and dissemination. One of the responsibilities in speech-language pathology is to faithfully capture the speech production characteristics of clinical populations so that informed management decisions may be made. Notation systems that are appropriately suited for this purpose are ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Children in this sample could produce approximately 80% of the 24 Australian English consonants (average of 19.10). Additionally, they could produce almost all (average of 19.62) of the 20 Australian English vowels (12-13 monophthongs and 7-8 diphthongs) (Cox, 2008;McLeod, 2007). However, the children in the current study demonstrated varying levels of severity and intelligibility.…”
Section: Ssd In a Sample Of Children Whose Parents And/or Teachers Armentioning
confidence: 99%
See 1 more Smart Citation
“…Children in this sample could produce approximately 80% of the 24 Australian English consonants (average of 19.10). Additionally, they could produce almost all (average of 19.62) of the 20 Australian English vowels (12-13 monophthongs and 7-8 diphthongs) (Cox, 2008;McLeod, 2007). However, the children in the current study demonstrated varying levels of severity and intelligibility.…”
Section: Ssd In a Sample Of Children Whose Parents And/or Teachers Armentioning
confidence: 99%
“…MD = Mitchell and Dellbridge (1965) symbols; HCE = (Harrington, Cox & Evans, 1997). The DEAP uses the MD symbols; however, recent acoustic analysis suggests that the HCE symbols are a more accurate representation of Australian English (see Cox, 2008). *Marginal = either correct on some but not all occasions, or an insufficient sample was obtained to determine consistency (typically only one example was obtained).…”
Section: Tablementioning
confidence: 99%